Description and ecology of a new species of the cricket genus Endecous (Orthoptera: Grylloidea: Phalangopsidae) in the speleological province of Arcos-Pains-Doresópolis, Southeastern Brazil - Castro-Souza, Rodrigo Antônio; Junta, Vitor Gabriel Pereira; Ferreira, Rodrigo Lopes (Zootaxa, 2020)
A new cricket species of the genus Endecous Saussure, 1878 is described in the present work found in the speleological province of Arcos-Pains-Doresópolis, which belongs to the limestone group Bambuí, Brazil. Moreover, the spatial distribution of the new species was related to the species Eidmanacris sp., which co-occurs with the former in several caves. Relationships between species abundance and horizontal projection, number of entrances and environmental stability of the caves where these species coexist were evaluated. The presence of bilateral symmetry in individuals of Endecous painensis n. sp. perhaps due to environmental stress caused by mining activities surrounding the cave was also tested. Endecous crickets are commonly observed in the caves, for which the preference by distinct microhabitats and generalist strategies may be key factors explaining colonization and segregation in relation to other cricket species in subterranean habitats. The generalist lifestyle of the here described species may attenuate the effects environmental stresses over development.